2006
DOI: 10.1152/ajpregu.00530.2005
|View full text |Cite
|
Sign up to set email alerts
|

Opiate slowing of feline respiratory rhythm and effects on putative medullary phase-regulating neurons

Abstract: Lalley, Peter M. Opiate slowing of feline respiratory rhythm and effects on putative medullary phase-regulating neurons. Am J Physiol Regul Integr Comp Physiol 290: R1387-R1396, 2006. First published November 10, 2005 doi:10.1152/ajpregu.00530.2005.-Opiates have effects on respiratory neurons that depress tidal volume and air exchange, reduce chest wall compliance, and slow rhythm. The most dose-sensitive opioid effect is slowing of the respiratory rhythm through mechanisms that have not been thoroughly inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 60 publications
(73 reference statements)
1
38
0
Order By: Relevance
“…Our finding that clinically relevant concentrations, which are in the nanomolar range, have no direct effect on respiratory premotor neurons is consistent with those of Lalley (2006), who used intracellular recordings from ventrolateral respiratory column neurons in barbiturate-anesthetized or decerebrate adult cats. Intravenous doses of the agonist fentanyl in the clinical dose range (3-7 g/kg) led to significant slowing of the respiratory rhythm as well as an increase in duration of discharge in inspiratory and expiratory bulbospinal and propriobulbar neurons.…”
Section: Only Supraclinical Doses Of Morphine Have a Direct Depressansupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding that clinically relevant concentrations, which are in the nanomolar range, have no direct effect on respiratory premotor neurons is consistent with those of Lalley (2006), who used intracellular recordings from ventrolateral respiratory column neurons in barbiturate-anesthetized or decerebrate adult cats. Intravenous doses of the agonist fentanyl in the clinical dose range (3-7 g/kg) led to significant slowing of the respiratory rhythm as well as an increase in duration of discharge in inspiratory and expiratory bulbospinal and propriobulbar neurons.…”
Section: Only Supraclinical Doses Of Morphine Have a Direct Depressansupporting
confidence: 90%
“…However, there were no changes in the intrinsic properties of the studied neurons; that is, there was no evidence from measurements of input resistance or action potential threshold, shape, and afterhyperpolarization that the doses of fentanyl that slowed rhythm acted on membrane conductances. Lalley (2006) suggested that slowing was evidently generated through effects on other neurons that control the onset and termination of inspiratory and expiratory neuron discharges, such as those in the pons and pre-Bötzinger complex.…”
Section: Only Supraclinical Doses Of Morphine Have a Direct Depressanmentioning
confidence: 99%
“…The latter are well-known pharmacological targets for anaesthesia and the treatment of pain. Clinically useful m-OR agonists, however, depress central respiratory activity, causing cessation of rhythmic breathing movements (Mellen et al 2003;Lalley 2006). An averting medical approach against opioidinduced apnoea is possible with 5-HT 4 R agonists that re-activate cellular AC (Manzke et al 2003), but such medication is so far not useful in men because ) to anaesthetized rats in vivo increased rRMA (red trace).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to measurement limitations, pharmacokinetics and pharmacodynamics seem to differ significantly between species for both intravenous anesthetics and opioids and seem subject to allometry (378). As a result, rodents (rats and mice) and other small mammals (rabbits) require much larger single doses (mg/kg) and infusion rates (mg/kg/h) of intravenous agents (61,482,491) and opioids (microgram/kg) (25,117,314,359,361,436,772,774) on a weight basis than larger mammals (dogs) and primates (humans). Finally, it is important to realize that only the free plasma concentrations in the aqueous phase of intravenous anesthetics or opioids seem to be relevant for the clinical effect, not the total plasma concentration.…”
Section: What Are Clinically Relevant Concentrations Of Anesthetics?mentioning
confidence: 99%
“…Both morphine and the more powerful synthetic opioids of the phenylpiperidine class (fentanyl, alfentanil, sufentanil, and remifentanil) lead to dose-dependent respiratory depression. At perioperative analgesic doses for humans (morphine 0.1-0.2 mg/kg, fentanyl 0.5-1 μg/kg, see Tables 2 and 6), which result in effect site concentrations in the low nanomolar range (see Table 6), the first sign of clinically relevant respiratory depression is a slowing in respiratory rate, which at higher doses of the synthetic fentanyl analogues (fentanyl > 3 μg/kg) will lead to apnea (359,361,362). Depression of tidal volume (TV) secondary to depression of the central chemoreflex and depression of excitatory drive from the brainstem to the inspiratory motoneurons is also apparent at analgesic doses but this often remains clinically unrecognized in spontaneously breathing subjects, because the hypoventilation leads to accumulation of PaCO 2 with a resultant increase in chemodrive and thus TV.…”
Section: Current Knowledge Of Opioid Agonists In Clinical Use For Anementioning
confidence: 99%